Educar para leer y leer para educar: alfabetización lectora en la asignatura documentación informativa - Bas Martín, Nicolás (Revista General de Información y Documentación, 2010)
Promoting the reading habit is one of the subjects which one has to retake of the Spanish University. In this sense, the New European Higher Education Area offers an appropriate framework for implementing new teaching methodologies to improve the reading levels of students. From studies carried out to students of the subject “Information Documentation” and results, we intend to learn about reality, the reading, which provides a sociological and cultural vision to face new challenges.
Keywords: Information Documentation; Reading; Reading literacy